Wildlife monitoring with drones: A survey of end users - Raymond B. Iglay; Landon R. Jones; Jared A. Elmore; Kristine O. Evans; Sathish Samiappan; Morgan B. Pfeiffer; Bradley F. Blackwell (Wildlife Society Bulletin, 2024)
Abstract Rapid advancements in technology often yield research inquiry into novel applications and drone (i.e., unoccupied aircraft systems or UAS) applications in wildlife management are no exception. We questioned the time lag between drone‐related research and end‐user assessments. We implemented an online, cross‐sectional survey of wildlife professionals to better understand current drone use and benefits or concerns, complemented by a review of contemporary peer‐reviewed and gray literature. We found little disparity between scientific inquiry and end‐user experiences (i.e., similar trends among concerns in published literature and survey results). Exploring new (i.e., advancements in computer vision) and refining original drone applications (i.e., evaluating animal behavior responses during monitoring) were strong among pilots of relatively minimal experience (1–5 years). Advancements in drone technology and changes in drone‐related legislation will continue to offer benefits and challenges.